2021
DOI: 10.1002/batt.202100179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Particles Morphology on the Electrochemical Performance of Na3V2(PO4)2F3‐yOy

Abstract: Among all the positive electrode materials explored for Na‐ion batteries, the family of Na3VIII2‐y(VIVO)y(PO4)2F3‐y (NVPFOy) has attracted extensive attention for its high operating voltage and structural stability. In order to promote better performance at high rates, it appears interesting to consider the correlation between NVPFOy’s composition, morphology (size and shape) and electrochemical properties. Here, solvothermal syntheses were considered in order to obtain a series of NVPFOy compounds showing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…14,36,41,56 Meanwhile, the broader signal for NVPFO 2 -Nano could be the consequence of disorder due to particle downsizing. 34 31 P ss-NMR spectra obtained for all NVPFO 2 show a very intense signal at ∼0 ppm corresponding to the P(OV 4+ ) 4 local environment (Fig. 5b).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…14,36,41,56 Meanwhile, the broader signal for NVPFO 2 -Nano could be the consequence of disorder due to particle downsizing. 34 31 P ss-NMR spectra obtained for all NVPFO 2 show a very intense signal at ∼0 ppm corresponding to the P(OV 4+ ) 4 local environment (Fig. 5b).…”
Section: Resultsmentioning
confidence: 96%
“…[22][23][24][25][26][27][28] and morphology design (flower, sand rose, nano/micro-sphere, nano/micro-cube, etc.) [29][30][31][32][33][34] have been proposed to overcome this problem. Among the various synthesis methods, morphology control and hybridization with a carbon-based conductive phase are often carried out by hydrothermal/solvothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 − 21 Recently, Fang et al, in 2022, reported morphological impact on Na 3 V 2 (PO 4 ) 2 F 3 cathode performances for Na-ion batteries. 22 The micro-/nanostructure morphology of the Na 3 V 2 (PO 4 ) 2 F 3 cathode designed by one-pot hydro-/solvothermal method without any high-temperature treatment has received great attention as it reduces the time, energy, and controls the particle size. 23 , 24 Recently, the synthesis of hierarchical micro-/nanostructures of Na 3 V 2 (PO 4 ) 2 F 3 morphology has attracted attention for designing Li-/Na-ion batteries due to their extraordinary properties that suppress particle agglomeration; low volume expansion leads to better electrical conductivity and diffusivity.…”
Section: Introductionmentioning
confidence: 99%